Wie kann der Investitionsschwäche in Deutschland steuerpolitischbegegnet werden? - Katharina Nicolay; Daniela Steinbrenner (Wirtschaftsdienst, 2023)
– Various obstacles, such as a shortage of skilled workers, high labour costs, high corporate taxes, as well as increasing regulatorydensity and high-energy costs, hamper investment in Germany. In particular, the lack of significant tax reforms has eroded Germany's tax at-tractiveness compared to other competitors, including France, the UK and the US in recent years. While the Growth Opportunities Act haspositive aspects such as the broadening of tax incentives for research and development and the extension of loss carry back regulations, itdoes not generally alleviate the issue of high corporate taxes in Germany. Additionally, it does not substantially reduce bureaucratic burdens forbusinesses, as some of its provisions may increase administrative complexity.
Keywords: H21; H25; 330; Investitionspolitik; Steuerpolitik; Deutschland; Investitionspolitik; Steuerpolitik; Deutschland